Introduction: making sense of digital diplomacy - Bjola, C (Routledge, 2015)
The recent spread of digital initiatives in foreign ministries is often argued to be nothing less than a revolution in the practice of diplomacy. In some respects this revolution is long overdue. Digital technology has changed the ways firms conduct business, individuals conduct social relations, and states conduct governance internally, but states are only just realizing its potential to change the ways all aspects of interstate interactions are conducted. In particular, the adoption of digital diplomacy (i.e., the use of social media for diplomatic purposes) has been implicated in changing practices of how diplomats engage in information management, public diplomacy, strategy planning, international negotiations or even crisis management. Despite these significant changes and the promise that digital diplomacy offers, little is known, from an analytical perspective, about how digital diplomacy works.